POSSIBILITIES OF A HAND: A PHENOMENOLOGICAL PERSPECTIVE - VYDROVÁ, Jaroslava (Studia Universitatis Babeș-Bolyai Philosophia, 2022)
Our starting point is a phenomenological analysis of the concepts of hand and possibility in relation to human realization and expression, whereby the problem of hand and its movements can be followed in this framework in its peculiarity and uniqueness. With regard to possibility, we follow a certain shift in Husserl’s concept of possibility towards practical possibility, as well as some selected passages in his texts concerning corporeality and constitution. This phenomenological starting point is connected to the question of stimulation (potentiating) of the hand in the creative process; we draw upon insights in texts of a Finnish thinker and architect Juhani Pallasmaa and on examples from fields of art, technology and handicrafts. The goal of the text is the return to the hand and the revival of the sphere of original realization of the man, as opposed to uniformity, excess of impulses, tendency to manipulate or, on the other hand, desensitization, whereby we want to open up a space for stimulation of creativity and deepening of the experience on this basis, whose starting point is, precisely, the phenomenological analysis.